To solve this system of equations, we can use the method of substitution or elimination. Let's use the substitution method in this case.
From the first equation:
-2x + y = 6
y = 2x + 6
Substitute y = 2x + 6 into the second equation:
4x - 2(2x + 6) = -12
4x - 4x - 12 = -12
-12 = -12
Since the equation simplifies to -12 = -12, it means that the system of equations has an infinite number of solutions. This is because the two equations represent the same line, so no matter what value of x and y you choose, it will satisfy both equations.
−2x+y=6 and 4x−2y=−12
1 answer